'• MAXIMIZACIÓN DE LA PERMEABILIDAD MAGNÉTICA DE BARRAS DE NUMETAL (Ni77Fe14CusMo4) PARA USO EN TECNOLOGÍA SATELITAL - Ferrero S., Gabriel (2005)
An experimental procedure has been developed to increase in a factor of 50 the magnetic permeabilitY of mumetal bars (Ni77Fe14Cu5Mo4). The procedure consists of a heat treatment under inert atmosphere, for which a programmable automatic temperature regulator of high precísion was designed and constructed. It has been verified that during the treatments the system is able to maintain a stable temperature of more than 1000 oc with an error smaller than 2 oc and with smaller linear gradients of 1%. In addition permeameter with electronic airflow meter was designed and constructed for monitoring the magnetic permeability. The treated bar was used to construct a magnetic pair (magnetic torquex) for satellite. The produced instrument develops a maximun magnetic dipole of 25 Am2 in its linear zone with a consumption of less than 0,3 W of power and one mass of 2,1 kg Taking advantage of the interaction between the magnetic pairs and the Earth's magnetic field is possible to introduce torque in a satellite in orbit for controlling its direction in the space.